A Modelica simulator to support the development of the control system of an autonomous All-Terrain mobile robot. Issue 1 (2015) - D'Amelio Luca Bascetta, Enzo L.; Cucci, Davide A.; Matteucci, Matteo; Bardaro, Gianluca
Abstract: This paper describes the development of a Modelica simulator of an All-Terrain vehicle using the Vehicle Dynamics Library. The model aims at replicating the behaviour of a Yamaha Grizzly 700 ATV, focusing on the dynamics that are relevant to the design and test of the vehicle control system. A thorough experimental validation of the simulator, demonstrating its accuracy in reproducing the behaviour of the experimental system, is also presented.